The Dilemma of Knowledge Transfer in Early Independent Indonesia - J. Thomas Lindblad (Universitas Gadjah Mada, 2021)
This article addresses the dilemma of knowledge transfer at the time of decolonization and early independence in Indonesian history. There was an urgently felt need to replace Dutch knowledge as far as possible with knowledge held by Indonesians or imported from foreign countries other than the Netherlands. Concurrently, from the time of Indonesia’s independence there was also a necessity to retain or gain access to practical knowledge required for economic development The article argues that this dilemma was resolved by a mix of policies geared towards different levels of sophistication of the knowledge involved. The article contains a brief theoretical treatment of this dilemma, followed by a global overview of policies implemented. A separate case study on the key banking sector serves to demonstrate the possibilities and constraints in effectuating a transfer of knowledge soon after independence.